A contribution on the subfamilies Helconinae, Homolobinae, Macrocentrinae, Meteorinae, and Orgilinae (Hymenoptera: Braconidae) of southeastern Anatolia with new records from other parts of Turkey - Beyarslan, Ahmet; Gozuacik, Celalettin; Ozgen, Inanc (Tubitak Scientific & Technological Research Council Turkey, 2013)
This study was carried out in order to determine the species of the subfamilies Homolobinae, Macrocentrinae, Meteorinae, and Orgilinae in southeastern Anatolia, Turkey. Malaise and light traps and sweeping nets were used to obtain adult specimens from various habitats in the study area during 2010 and 2011. The collected materials from southeastern Anatolia and from new localities of other regions were identified and a total of 11 species from 5 genera determined, of which the species Diospilus morosus Reinhard is a new record for southeastern Anatolia. All species are new records on the basis of provinces of Turkey. The distributions of the species were evaluated considering the zoogeographic regions.
Keywords: Homolobinae; Macrocentrinae; Meteorinae; Orgilinae; Fauna; southeastern Anatolia; Turkey